2019
DOI: 10.1080/13102818.2019.1611385
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity, mechanism of action, and methods for stabilisation of defensins as new therapeutic agents

Abstract: Bioactive compounds, such as antimicrobial peptides (AMPs), have increasingly been used recently to counteract the rapidly increasing incidence of bacterial resistance to usual antibiotics and chemotherapeutics. In humans, endogenous AMPs are part of the immune system and act against pathogens. Defensins compose a class of AMPs that have activity against gram-positive and-negative bacteria, viruses, and fungi. For some, antitumour activity has also been reported. Such characteristics indicate that they represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 75 publications
1
70
0
2
Order By: Relevance
“…As previously reported [13,14,28], AMPs, including protamine, kill bacteria by acting on bacterial membranes or cell walls. Generally, AMP is amphiphilic and positively charged and has both hydrophobic and hydrophilic parts [12,16].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…As previously reported [13,14,28], AMPs, including protamine, kill bacteria by acting on bacterial membranes or cell walls. Generally, AMP is amphiphilic and positively charged and has both hydrophobic and hydrophilic parts [12,16].…”
Section: Discussionmentioning
confidence: 57%
“…AMPs are the host defense peptides and are key elements of innate immunity [12]. Targeting of the bacterial membrane and the concomitant loss of membrane integrity is a well-accepted mechanism of action of AMPs [13,14]. In addition, several reports demonstrated that AMPs can disturb a series of cellular processes and metabolic functions [15].…”
Section: Introductionmentioning
confidence: 99%
“…Terms such as anti-bacterial or anti-fungal are used for antimicrobial compounds that inhibit specific groups of microbes, namely anti-bacteria for bacteria and anti-fungal for fungi. Two mechanisms are primarily due to the antibacterial behavior of an agent, which involves chemically interfering with the synthesis or function of essential components of bacteria and/or circumventing traditional antibacterial resistance mechanisms (Amerikova et al, 2019;Gonelimali et al, 2018;Khameneh et al, 2019). There are many targets for antibacterial agents, including bacterial protein biosynthesis; bacterial cell-wall biosynthesis; degradation of bacterial cell membranes; replication and repair of bacterial DNA; and inhibition of a metabolic pathway (Khameneh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few antimicrobial agents available to battle these pathogens 1 , 2 , 5 , and it is not just a question of availability and diversity of these compounds, it is also a question of which cellular mechanisms they may target. In that respect, the current options are very limited and need urgent expansion 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%